Falsely low immunoglobulin (Ig)G4 in routine analysis: how not to miss IgG4 disease. (9th August 2016) - Egner, W.; Swallow, K.; Lock, R. J.; Patel, D.
Summary: Immunoglobulin (Ig)G4 disease can have apparently 'normal' levels of IgG4 due to antigen excess conditions. IgG4 measurement therefore appears falsely low. UK National External Quality Assurance Scheme (UK NEQAS) data and other reports have suggested that this problem occurred despite pre‐existing antigen excess detection steps. To determine the clinical relevance of the problem, we examined the prevalence and characteristics of prozoning in our laboratory and patient cohorts. We establish that the prevalence of raised IgG4 in routine IgG4 analysis is low (< 1%) using one of the two routine methods in use in the United Kingdom. We show that subsequent assay modification appears to have reduced the likelihood of misleading readings. However, the original version of the assay prozoned to low levels (below 0·64 g/l) in 41% of high IgG4 samples in our patients. This may explain the previous reports of low sensitivity of raised IgG4 for IgG4RD, and predictive values should be re‐evaluated in this disease using modified prozone‐resistant protocols. All laboratories providing IgG4 measurements should verify that their assays are fit for the clinical quality requirement of detection raised IgG4 levels and must verify the upper limit of their reference ranges and freedom from prozoning.